PENINGKATAN KUALITAS HIDUP MASYARAKAT PESISIR MELALUI LITERASI KESEHATAN MENTAL DI DESA BANARAN - Yuliasari, Hesty; Nirmalasari, Novita; Fatimah, Malida; Pusvitasari, Putri (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
One of the problems experienced by coastal communities in Banaran Village is limited access to education, health care, and public services, which impact the dynamics and well-being of life. The limited access to health care, particularly mental health, significantly impacts the community's quality of life. This is especially true in villages far from the city and experiencing economic instability. Individuals with a quality of life are better able to manage themselves and the problems they face. Therefore, knowledge about mental health is needed so that coastal communities have the same knowledge as other communities. Coastal communities are a vulnerable group due to a lack of mental health literacy. Therefore, mental health literacy is one solution to improving the quality of life of coastal communities. The goal of this activity is to improve the quality of life of coastal communities through Mental Health Literacy. The method used is training that includes education and role-play through self-assessment. The results showed a difference in participants' understanding and skills after being provided with education and role-play on mental health literacy. This increase in cognitive skills allows individuals to think clearly and identify alternative solutions to their problems, thus encouraging them to seek the most effective solutions to avoid conditions that cause mental disorders. Mental health literacy is an alternative solution to problems that can improve the community's quality of life.